Evaluation of the Council to Improve Foodborne Outbreak Response (CIFOR) Guidelines for Foodborne Disease Outbreak Response and Associated Toolkit - Ringel, Jeanne S. (RAND Corporation, 2013)
With reducing the burden of foodborne disease among its primary goals, the multidisciplinary Council to Improve Foodborne Outbreak Response (CIFOR) developed the Guidelines for Foodborne Outbreak Response (2009) and a companion Toolkit (2011) to improve foodborne disease outbreak detection and response at the state and local levels. This study assesses the distribution and use of the CIFOR Guidelines and Toolkit to determine whether and to what extent they are reaching their intended users and achieving their goals.